2010
DOI: 10.11646/zootaxa.2497.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The problems with Polypedilum Kieffer (Diptera: Chironomidae), with the description of Probolum subgen. n.

Abstract: A phylogenetic analysis of the genus Polypedilum Kieffer utilizing only species with known larvae, and including one additional species presumed to belong to a new subgenus was performed. The subgenera Tripodura Townes, 1945, Pentapedilum Kieffer, 1913 and Cerobregma Sæther et Sundal, 1999, were all monophyletic, while Uresipedilum Oyewo et Sæther, 1998 was monophyletic when the new subgenus Probolum was excluded. Polypedilum s. str. was never monophyletic even when excluding the atypical P. nubifer (Skuse, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…In addition to these important differences in bands pattern and general organization of active regions between both Nigerian and Malawian populations, similarities in the organization of the chromosomes were hardly observed in comparison to other published karyotypes in the genus Polypedilum (Porter and Martin 1977, Kerkis et al 1996). The genus Polypedilum is actually very diverse with 8 subgenera described (Saether et al 2010) and this could explain the poor similarity observed in the karyotypes between species spread over these subgenera.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these important differences in bands pattern and general organization of active regions between both Nigerian and Malawian populations, similarities in the organization of the chromosomes were hardly observed in comparison to other published karyotypes in the genus Polypedilum (Porter and Martin 1977, Kerkis et al 1996). The genus Polypedilum is actually very diverse with 8 subgenera described (Saether et al 2010) and this could explain the poor similarity observed in the karyotypes between species spread over these subgenera.…”
Section: Resultsmentioning
confidence: 99%
“…Many descriptions are of single species based on the adult male alone, but synthesis and reconciliation with immature stages has progressed, e.g. by Saether et al (2010), Epler et al (2013) and Ekrem et al (2017). In Asia, studies of adults predominate (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The larvae mostly occur in sediments, with a few species mining wood or grazing epilignic and epilithic surfaces (Cranston et al 1989). At present, the genus Polypedilum comprises eight subgenera: Polypedilum Kieffer, 1912, Pentapedilum Kieffer, 1913, Kribionympha Kieffer, 1921, Tripedilum Kieffer, 1921, Tripodura Townes, 1945, Uresipedilum Oyewo & Sæther, 1998, Cerobregma Sæther & Sundal, 1999 and Probolum Andersen & Sæther 2010 (Sæther et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Wang (2004) reviewed the subgenus on the basis of 14 species recorded in China. Sæther and Oyewo (2008) and Sæther et al (2010) revised the subgenus around the world and transferred Polypedilum (Uresipedilum) bullum Zhang & Wang, 2004, Polypedilum (Uresipedilum) pedatum excelsius Townes, 1945 and Polypedilum (Uresipedilum) simantokeleum Sasa, Suzuki & Sakai, 1998 to the newly proposed subgenus Probolum . Up to date, Uresipedilum includes 46 known species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation